Multiple myeloma during pregnancy as a challenge in clinical practice – a review - Szydełko, Magdalena; Szydełko, Joanna; Litwińczuk, Michał (Journal of Education, Health and Sport, 2019)
Introduction: Multiple myeloma (MM) is a hematological malignancy characterized by an abnormal proliferation and accumulation of monoclonal plasma cells. MM typically affects the elderly people with the median age at the diagnosis between 65 to 74 years. Only in < 2% of cases it is observed <40 years, that is why its incidence in gestation is extraordinary. Aim of the study: The aim of this study was to present the review of the literature concerning the cases of MM in pregnancy as a great challenge in clinical practice. Moreover, the most common symptoms, diagnostic as well as therapeutic strategies of MM in pregnancy were discussed. The influence of the status of the newborns and the pregnant women were also analyzed. Description of knowledge: Our overview revealed 44 cases of MM in pregnancy. It was predominantly diagnosed in the 2nd or 3rd trimester and the median age of women was 34 years. The caesarean section seemed to be the recommended method of delivery and the mean gestational age at the delivery was 35. hbd. Nearly all of the newborns were born premature, but healthy. The symptoms were similar to those in the general population (bone pain, signs of anemia, hypercalcemia) and in single cases the renal failure, hypertensive or bilateral breast lumps were observed. Steroids were predominantly administered and the therapy based on cyclophosphamide, urethane or interferon was the rarity.Conclusions: MM in pregnancy seems not be a contraindication for maintaining of gestation. The management may be problematic due to the lack of guidelines concerning the methods of treatment as well as its safety for the fetus. Based on the literature, steroids are the most certain and efficient anti-MM drugs in pregnancy. However, the majority of newborns are premature, which is also associated with the possibility of later complications.